Análise comparativa da estabilidade inicial e tardia de dois implantes retentores de sobredentadura mandibular submetidos à carga imediata, por meio de frequência de ressonância: acompanhamento de 36 meses - André, Rodolfo Alexandre (2012)
The effectiveness of two implant-supported overdentures in the mandibular arch in a twostage surgical procedure is well documented in the literature. However, there is a lack of consensus on immediate loading protocols for this option. The aim of this study was to evaluate initial and late stability of mandibular, implant-supported overdentures, when the complete denture used by the patient was considered satisfactory and readapted. The sample was composed by 11 patients of both genders (mean age 57 years-old). All surgical procedures and prosthetic reconstructions were made by the same professional. Implant placement was standardized according to a paralleling device and symmetrical to the median line. All implants had 4 mm in diameter. The abutments were installed, and pick-up procedures made with the own patient s complete prosthesis. Bars and definitive prostheses were installed within 24 hours. Initial implant stability was evaluated by resonance frequency analysis (OsstellTM) with a ISQ mean of 78.3. Values were registered after 4, 7, 12, and 36 months, with mean ISQ values of 73.7, 73.6, 74.2, and 73.2, respectively. Implant and prosthesis reported success rates of 100%.A significant reduction in ISQ values (5.9%) was observed between initial moment and 4 months later. However, no significant statistical differences in ISQ values were observed among the subsequent observation periods.